Exploring the current molecular landscape and management of multiple myeloma patients with the t(11;14) translocation - Diamantidis, Michael D.; Papadaki, Sofia; Hatjiharissi, Evdoxia (Frontiers in Oncology, 2022)
Multiple myeloma (MM) is a genetically complex disease. The key myeloma-initiating genetic events are hyperdiploidy and translocations involving the immunoglobulin heavy chain (IgH) enhancer on chromosome 14, which leads to the activation of oncogenes (e.g., CCND1, CCND3, MAF and MMSET). The t(11;14) translocation is the most common in MM (15-20%) and results in cyclin D1 (CCND1) up-regulation, which leads to kinase activation and tumor cell proliferation. Notably, t(11;14) occurs at a higher rate in patients with plasma cell leukemia (40%) and light chain amyloidosis (50%). Patients with myeloma who harbor the t(11;14) translocation have high levels of the anti-apoptotic protein BCL2. Multiple studies demonstrated that the presence of t(11;14) was predictive of BCL2 dependency, suggesting that BCL2 could be a target in this subtype of myeloma. Venetoclax, an oral BCL2 inhibitor, has shown remarkable activity in treating relapsed/refractory MM patients with t(11;14) and BCL2 overexpression, either as monotherapy or in combination with other anti-myeloma agents. In this review, we describe the molecular defects associated with the t(11;14), bring into question the standard cytogenetic risk of myeloma patients harboring t(11;14), summarize current efficacy and safety data of targeted venetoclax-based therapies and discuss the future of individualized or precision medicine for this unique myeloma subgroup, which will guide optimal treatment.